Biodegradable magnesium alloys for medical application - Papirov, I.I.; Tikhonovsky, M.A.; Kutniy, K.V.; Pikalov, A.I.; Sivtsov, S.V.; Pizizhenko, L.A.; Shokurov, V.S. (Functional Materials, 2008)
The microstructure, mechanical properties and dissolution rate of magnesium alloy WE43 at various microstructure parameters in the medium simulating biological fluid have been studied. In order to improve the alloy mechanical properties by ultra-fine grained structure formation, the equal-channel angular pressing was used followed drawing and heat treatment.